Closed curtain - Panahi, Jafar 1960-; Partuwī, Kāmbūzyā 1955-2020; Jahanpanah, Mohammad Reza ca. 20. Jh; Moqadam, Maryam 1970- (New Wave Films, 2015)
In a secluded house by the sea with the curtains shut, a screenwriter hides from the world with only his dog as company. The tranquility is abruptly broken one night by the arrival of a young woman fleeing from the authorities. Refusing to leave, she takes refuge in the house. But come dawn, another unexpected presence will change everything.
Original: Iran 2013
Keywords: DVD-Video